Targeting Chitinase 1 and Chitinase 3-Like 1 as Novel Therapeutic Strategy of Pulmonary Fibrosis - Lee, Suh-Young; Lee, Chang-Min; Ma, Bing; Kamle, Suchitra; Elias, Jack A.; Zhou, Yang; Lee, Chun Geun (Frontiers in Pharmacology, 2022)
Chitinase 1 (CHIT1) and Chitinase 3-like-1 (CHI3L1), two representative members of 18-Glycosyl hydrolases family, are significantly implicated in the pathogenesis of various human diseases characterized by inflammation and remodeling. Notably, dysregulated expression of CHIT1 and CHI3L1 was noted in the patients with pulmonary fibrosis and their levels were inversely correlated with clinical outcome of the patients. CHIT1 and CHI3L1, mainly expressed in alveolar macrophages, regulate profibrotic macrophage activation, fibroblast proliferation and myofibroblast transformation, and TGF-beta signaling and effector fucntion. Although the mechanism or the pathways that CHIT1 and CHI3L1 use to regulate pulmonary fibrosis have not been fully understood yet, these studies identify CHIT1 and CHI3L1 as significant modulators of fibroproliferative responses leading to persistent and progressive pulmonary fibrosis. These studies suggest a possibility that CHIT1 and CHI3L1 could be reasonable therapeutic targets to intervene or reverse established pulmonary fibrosis. In this review, we will discuss specific roles and regulatory mechanisms of CHIT1 and CHI3L1 in profibrotic cell and tissue responses as novel therapeutic targets of pulmonary fibrosis.